The Effect of Extraction Time of Raja Nangka Banana Peel as Capping Agent on the Characteristic and Antibacterial Activity of ZnO Nanoparticles Against Staphylococcus epidermidis - Adinnia Apriandini; Fajaroh, Fauziatul; Aliyatulmuna, Adilah; Ciptawati, Endang (Al-Kimia, 2022)
A green chemistry-based ZnO nanoparticle synthesis method based on plant extracts has been developed. Raja nangka banana peel is one of them. The extraction time is one of the elements that influences the amounts of secondary metabolites. The longer the extraction time, the more secondary metabolites are obtained. If the optimal time is exceeded, the secondary metabolite compounds will decrease. The purpose of this research was to determine the optimal time to extract secondary metabolites from the raja nangka banana peel and to know the effect of extraction time on the characteristics of ZnO nanoparticles, which include morphology, size, and antibacterial activity against Staphylococcus epidermidis. The steps of this research: maceration, phytochemical tests and total levels tests, synthesis of ZnO nanoparticles, characterization, and antibacterial activity test against Staphylococcus epidermidis. Maceration for 24 hours is the best time for extracting secondary metabolites from raja nangka banana peels. The SEM test results show that the morphology of the three samples had agglomeration. The ZnO nanoparticles with 24-hour raja nangka banana peel extract had a smaller size of 295.2 nm and were spherical. Inhibition zone diameter from ZnO nanoparticles with 24-hour raja nangka banana peel extract has a larger area of 5.65 mm.